Incidence and Predictors of Relapse After Stopping Antiviral Therapy in Pediatric Chronic Hepatitis B. Issue 9 (7th June 2022) - Upadhyay, Piyush; Lal, Bikrant Bihari; Sood, Vikrant; Khanna, Rajeev; Gupta, Ekta; Rastogi, Archana; Alam, Seema
Abstract : Background: There are no definite end-points for stopping therapy in pediatric chronic hepatitis B (CHB). The study objective was to evaluate the incidence of relapse after stopping antiviral therapy and to identify its predictors. Methods: All hepatitis B surface antigen (HBsAg) positive children presenting to our hospital, who had been on antivirals for at least 2 years with undetectable hepatitis B virus-deoxyribonucleic acid (HBV-DNA) and normal alanine aminotransferase (ALT) on 3 consecutive occasions over last 12 months were included. Antivirals were stopped if liver biopsy showed histological activity index <5 and fibrosis (Ishak) <3. Virological relapse was defined as the elevation of HBV-DNA (>2000 IU/mL) and biochemical relapse as a rise in ALT levels to >2 times the upper limit of normal. Those having biochemical relapse were started on pegylated interferon alpha-2b-based sequential therapy. Results: Of the 114 children with CHB screened, 31 HBsAg-positive children fulfilled inclusion criteria and antivirals were stopped in them. Virological and biochemical relapse was seen in 12 (38.7%) and 5 (16.1%) children within 12 months of stopping antiviral treatment. On Cox regression, hepatitis B e antigen (HBeAg) positive status at the time of stopping antiviral therapy (HR: 6.208, 95% CI: 1.630–23.638) and longer time taken for HBV-DNA to become undetectable while on antivirals (HR: 1.027, 95% CI: 1.000–1.055) were the independent predictors of relapse. Conclusion: Discontinuation of antiviral treatment in children with CHB resulted in relapse in one-third of the patients. Relapse was frequent in those who were HBeAg-positive at the time of stopping therapy and in those who required longer therapy for HBV-DNA to become undetectable.